Estudo numérico de problemas acoplados envolvendo a resposta dinâmica das estruturas - Andretta, Erli Raquel Zortea (2017)
In the design of a structural design, which is necessary to quantify the wind action on a structure, many uncertainties still involve the behavior and performance of the buildings, making it difficult for the calculating engineer to predict the true load to be used. Understanding this behavior enables the prevention of harmful effects on the structure, as well as increasing its useful life and reducing pathologies. In this work a study was carried out to prepare a welded metallic portico of four floors, to perform experimental and computational tests to verify the dynamic behavior of the exposed structure to the action of the fluid flow. For the experimental tests of the modal analysis, the portico was considered set, where it was sought to identify the vibration modes of flexion. The computational evaluations performed in this work use models of finite elements and finite volumes. In the modal analysis performed through simulation, it was possible to identify some modes of flexion, which were compared with those performed experimentally, presenting a good correlation, validating the model. The fluid flow simulation was performed, focusing on the metallic portico, making it possible to verify the structure response when exposed to this type of flow.